Priorities for methodological research on patient and public involvement in clinical trials: A modified Delphi process. - Kearney, A; Williamson, P; Young, B; Bagley, H; Gamble, C; Denegri, S; Muir, D; Simon, N; Thomas, S; Elliot, J; Bulbeck, H; Crocker, J; et al. (Wiley, 2017)
Background Despite increasing international interest, there is a lack of evidence about the most efficient, effective and acceptable ways to implement patient and public involvement (PPI) in clinical trials. Objective To identify the priorities of UK PPI stakeholders for methodological research to help resolve uncertainties about PPI in clinical trials. Design A modified Delphi process including a two round online survey and a stakeholder consensus meeting. Participants In total, 237 people registered of whom 219 (92%) completed the first round. One hundred and eighty-seven of 219 (85%) completed the second; 25 stakeholders attended the consensus meeting. Results Round 1 of the survey comprised 36 topics; 42 topics were considered in round 2 and at the consensus meeting. Approximately 96% of meeting participants rated the top three topics as equally important. These were as follows: developing strong and productive working relationships between researchers and PPI contributors; exploring PPI practices in selecting trial outcomes of importance to patients; and a systematic review of PPI activity to improve the accessibility and usefulness of trial information (eg participant information sheets) for participants. Conclusions The prioritized methodological research topics indicate important areas of uncertainty about PPI in trials. Addressing these uncertainties will be critical to enhancing PPI. Our findings should be used in the planning and funding of PPI in clinical trials to help focus research efforts and minimize waste.